The wars of independence 1249-1328 - Duck, Michèle S. (Connecting history, 2022)
Exam board: SQA Level: Higher Subject: History First teaching: September 2018 First exam: Summer 2019 Fresh stories, fresh scholarship and a fresh structure. Connecting History informs and empowers tomorrow's citizens, today. Bringing together lesser-told narratives, academic excellence, accessibility and a sharp focus on assessment success, this series provides a rich, relevant and representative History curriculum. > Connect the past to the present. Overarching themes of social justice, equality, change and power help students to understand the importance of events and issues, then and now. > Go far beyond other resources. With respect and aspiration for the transformative power of History, this series incorporates the latest research, challenges old interpretations and embeds diverse experiences throughout. > Follow a clear and consistent structure. The key issues in the specification form the chapters in each book, and the content descriptors are subheadings within the chapters. Finding the information that you need has never been easier. > Meet the demands of the assessments. Connecting History develops the knowledge and skills for success, with appropriate breadth, depth and pace. The narrative and sources take centre stage and the authors model the process of answering questions effectively through that narrative, ensuring that students have enough key points to achieve full marks. End-of-chapter activities consolidate and extend learning. > Benefit from pedagogic and academic expertise. The authors are highly experienced teachers and examiners who know how to spark critical curiosity in students. Each book has been rigorously reviewed by an academic from the University of Glasgow, so you can rest assured that the content is accurate and up to date.